The effect of body weight on fresh sperm movement characteristics in African catfish (Clarias gariepinus) - Abdullah, Ramli; Khadijah, W.E.W.; Azlina, K.N. (2011)
Fresh sperm of African catfish were analysed with the aim to determine sperm movement characteristics based on individual fish body weight. Three Body Weight (BW) of fish were grouped as small (<1 kg), medium (1-1.5 kg) and large (>1.5 kg). The fish was sacrificed (euthanasia) and semen was collected by perforation of the testis. Large Body Weight (BW) of African catfish gave the highest fresh sperm total motility (82.40 +/- 4.59%) followed by medium body weight (51.64 +/- 9.82%) and small body weight (40.40 +/- 12.16%). In sperm velocity distributions, the values for rapid, medium, slow and static velocity for fresh sperm were ranged from 14.00 +/- 6.63 to 25.80 +/- 4.97, 5.60 +/- 2.32 to 15.40 +/- 2.82, 20.80 +/- 6.49 to 41.20 +/- 5.18 and 17.60 +/- 4.59 to 59.60 +/- 12.16%, respectively. The values of VAP (83.34 +/- 9.31 mu m sec(-1)), VSL (73.44 +/- 11.60 mu m sec(-1)) and VCL (108.12 +/- 5.51 mu m sec(-1)) for small body weight group were significantly higher (p<0.05) than those of the large body weight group (49.70 +/- 6.42, 41.90 +/- 4.94 and 74.60 +/- 9.47 mu m sec(-1), respectively). It is concluded that larger body weight of the fish gives better sperm quality compared to medium and small BW.